Lung microbiome and antimicrobial resistome of bronchiectasis patients attending a clinic at a tertiary academic hospital in Pretoria, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2022)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2022.